Strengthening Character Education Based on Online Learning for University Students Pasca Covid-19 - Asdar; Yuriatson Jubhari; Taufiq Natsir; A.Vivit Anggreani; Luana Sasabone; Tuan Nordin bin Tuan Kechik (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2023)
This study aimed to strengthen character education based on online learning for university students pasca covid-19. This study applied the qualitative research. This study was carried out at Universitas Bosowa students and lecturers. Results of study showed that character education is implemented pasca Covid-19 epidemic utilizing a distance learning approach (online), which was internet-based. The incorporation of character education based on online learning has an impact on attributes like religiosity, honesty, tolerance, discipline, hard work, creativity, independence, democracy, curiosity, national spirit, peace-loving, social obligation, and responsibility. Character education based on online learning can have an impact on how children develop their moral beliefs, integrity, critical thinking, independence, participation in other activities, and responsibility. It can be concluded that a distant learning method (online) was used to implement character education under the circumstances of the Covid-19 pandemic. Although there are some technical issues with using this system, and overall it can be used successfully.